2012
DOI: 10.1364/oe.20.00a190
|View full text |Cite
|
Sign up to set email alerts
|

Immersed finger-type indium tin oxide ohmic contacts on p-GaN photoelectrodes for photoelectrochemical hydrogen generation

Abstract: In this study, we demonstrated photoelectrochemical (PEC) hydrogen generation using p-GaN photoelectrodes associated with immersed finger-type indium tin oxide (IF-ITO) ohmic contacts. The IF-ITO/p-GaN photoelectrode scheme exhibits higher photocurrent and gas generation rate compared with p-GaN photoelectrodes without IF-ITO ohmic contacts. In addition, the critical external bias for detectable hydrogen generation can be effectively reduced by the use of IF-ITO ohmic contacts. This finding can be attributed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Current–voltage plots obtained from the model photoanode of the V RHE type are provided in Figure a. However, one may also plot the current–voltage characteristics of the photoanode with respect to the bias applied directly across the semiconductor–liquid junction ( V A ), a concept widely used in practice by the solid-state device community. , Under illumination and in the dark, the applied bias can be experimentally extracted as ,,, Current–voltage plots obtained from our model photoanode plotted with respect to V A are given in Figure b. Importantly, current–voltage plots with respect to V A and V RHE can be combined to extract important information directly related to the electrostatic and electrochemical potential changes ( V ph and Δ V F ) present under illumination.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Current–voltage plots obtained from the model photoanode of the V RHE type are provided in Figure a. However, one may also plot the current–voltage characteristics of the photoanode with respect to the bias applied directly across the semiconductor–liquid junction ( V A ), a concept widely used in practice by the solid-state device community. , Under illumination and in the dark, the applied bias can be experimentally extracted as ,,, Current–voltage plots obtained from our model photoanode plotted with respect to V A are given in Figure b. Importantly, current–voltage plots with respect to V A and V RHE can be combined to extract important information directly related to the electrostatic and electrochemical potential changes ( V ph and Δ V F ) present under illumination.…”
Section: Resultsmentioning
confidence: 99%
“…However, one may also plot the current−voltage characteristics of the photoanode with respect to the bias applied directly across the semiconductor−liquid junction (V A ), a concept widely used in practice by the solidstate device community. 67,68 Under illumination and in the dark, the applied bias can be experimentally extracted as 20,29,79,80 The illuminated and dark reference electrode potentials, which achieve an equivalent current of 0.067 mA/cm 2 , are represented by V RHE light and V RHE dark , respectively. The potential difference between V RHE light and V RHE dark is indicated as the PEC voltage ΔV F .…”
Section: Methodsmentioning
confidence: 99%
“…For instance, some groups reported that the III–V photoelectrodes integrated with solar cells could demonstrate extremely high solar-to-hydrogen efficiency. III-nitride semiconductors, especially Ga x In 1– x N ( E g : 3.4–0.7 eV), can harvest the entire visible light spectrum by controlling the ratio of gallium and indium. The low indium-containing Ga x In 1– x N possesses suitable band edge positions. This characteristic makes it possible to use the Ga x In 1– x N-based photoelectrodes to drive the overall water splitting under sunlight illumination. Although the III-nitride semiconductors grown by metal–organic chemical vapor deposition (MOCVD) possess high crystal quality, the PEC performances using the III-nitride-based photoelectrodes still suffer from severe bulk recombination and photocorrosion. In order to minimize the recombination losses, utilizing the geometry structure with lateral size less than the diffusion length of the minority carriers of GaN for PEC water splitting has been studied by several groups. The nanostructure of GaN photoelectrodes benefit the extraction of the photogenerated carriers, while the drawback is the extra photovoltage loss induced by the excess surface area and/or defects. , Another strategy to address the charge recombination is applying a p–n junction on the photoelectrodes.…”
Section: Introductionmentioning
confidence: 99%
“…The holes at the interface not only oxidize water (OER) but oxidize the photoelectrode. On the other hand, in p-type materials the band-bending promotes photo-generated electrons to transfer to the electrolyte where they participate in the HER process that almost leaves intact the surface of the photo-electrode chemically (Aryal et al, 2010;Rajeshwar, 2008;Liu et al, 2012). The p-type III-N materials as photoelectrodes have been less investigated in the photo-electrochemical process.…”
Section: Introductionmentioning
confidence: 99%